2007
DOI: 10.1080/00218460701585840
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion at Poly(Butylacrylate)–Poly(Dimethylsiloxane) Interfaces

Abstract: We present an investigation of the adhesion modulation mechanisms of silica-like nanoparticles (MQ resins) incorporated in polydimethylsiloxane (PDMS) elastomers and acrylic adhesives. The Johnson-Kendall-Roberts (JKR) test has been used to gain information on the both zero velocity and the velocity dependence of the adhesive strength, avoiding as much as possible contributions to the adhesive strength of bulk dissipation in the adhesive (which is not the case with peel tests). As the incorporation of the MQ r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…To minimize the influence of the solvent (octamethyltrisiloxane, boiling point 153 °C), the MQ resin containing PDMS was cured at 155 °C for 2 h. In all cases, the Young's moduli of the V‐PDMS/H‐PDMS mixtures were increased by increasing the ratio of the MQ resin. Similar results have been reported previously . It has also been noted that in the case of polymer‐filler hybrid systems, the modulus of the polymers was increased by strong interactions between the polymers and filler .…”
Section: Resultssupporting
confidence: 90%
“…To minimize the influence of the solvent (octamethyltrisiloxane, boiling point 153 °C), the MQ resin containing PDMS was cured at 155 °C for 2 h. In all cases, the Young's moduli of the V‐PDMS/H‐PDMS mixtures were increased by increasing the ratio of the MQ resin. Similar results have been reported previously . It has also been noted that in the case of polymer‐filler hybrid systems, the modulus of the polymers was increased by strong interactions between the polymers and filler .…”
Section: Resultssupporting
confidence: 90%
“…Johnson, Kendall, and Roberts demonstrated that even under zero external load, a gain of interfacial energy in the contact zone establishes a finite contact area between two rubber spheres. Since then, the JKR theory has become a staple in characterizing mechanical properties and adhesion of soft materials [10][11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%